Activation spectroscopy of electronically induced defects in solid Ne: Spectroscopy in Cryocrystals and Matrices - Grigorashchenko, O.N.; Rudenkov, V.V.; Khizhnyi, I.V.; Savchenko, E.V.; Frankowski, M.; Smith-Gicklhorn, A.M.; Beyer, M.K.; Bondybey, V.E. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2003)
Thermally stimulated luminescence (TSL) and thermally stimulated exoelectron emission (TSEE) methods were used in combination with cathodoluminescence to probe electronically induced defects in solid Ne. The defects were generated by a low energy electron beam. For spectroscopicstudy we used Ar* centers in Ne matrix as a model system. At a temperature of 10.5 K a sharp decrease in the intensity of "defect" components in the luminescence spectrum was observed.From the analysis of the corresponding peak in the TSL and TSEE yields the trap depth energy was estimated and compared with available theoretical calculations. The obtained data support the model suggested by Song, that stable electronically induced defects have the configuration of second-neighbour Frenkel pairs.